SMALL INDUSTRIAL ZONES: A NEW APPROACH TO INVESTMENT DEVELOPMENT IN THE REPUBLIC OF UZBEKISTAN - Salimov Bokhodir Bakhtiyorovich, Fayzikhodjaeva Mavluda Lutfullaevna, Arslanbekov Sayfulla Mamurjonovich, Egamberdiev Odiljon Buribaevich, Shonazarova Nilufar Baratovna (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This article describes the theoretical and economic foundations of the concept of free economic zones. The experience of foreign countries (Japan, South Korea, China, USA, and Russia) has been analyzed and the relevant conclusions are formulated. In addition, conclusions and recommendations on further improvement of the organizational structure of the free economic zones were pinpointed.